PRODUKSI PROGRAM DAKWAH DI CHANAL YOUTUBE : DA'WAH PROGRAM PRODUCTION ON YOUTUBE CHANNEL (STUDY ON THE PROGRAM SUBUH REACHING MUNZALAN BLESSINGS TV AT THE KAPALMUNZALAN MOSQUE IN INDONESIA) - Bob Andrian Bob Andrian; Doni Rifansyah Doni Rifansyah; Pilga ayong Sari Pilga ayong Sari (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
This research is related to the production process carried out by the Munzalan TV youtube channel on the dawn program reaching blessings. The focus of this research is to find out how the production process is carried out from pre-production to post-production carried out by Munzalan TV.  The approach used in this study is to use a qualitative approach with a descriptive method. In collecting data, researchers use several techniques, namely observation, interviews and documentation. The research was carried out at the mosque of the munzalan ship indinesia Road. Sungai Raya in Gg. Imaduddin, West Kalimantan, Indonesia. The results of this study are to describe how the production process includes pre-production, production and post-production carried out by Munzalan TV On the dawn program to achieve blessings. In general, the results of this study show that the production process carried out by Munzalan TV uses three stages, the first pre-production at this stage the first is syuro, then prepare room control, prepare production equipment at this stage the image director must set the exposure segitigs, then prepare the sound, the next stage of production, at the time of production carried out is to prepare Youtube straming using sofwara vMix, then for the production image director no longer do the camera settings have stayed in one direction only, then the sound control that is carried out by the mosque takmir and connects to the soundcar which is the responsibility of the stramer and for the stylist cahata control there is no lightingman because hanaya uses mosque lighting, at the time of production also do records that are part of post-production,  In the post-production stage, what is done is editing and airing.